The Part Played by Platelets in the Formation of an Efficient Hemostatic Plug - Roskam, J; Hugues, J; Bounameaux, Y; Salmon, J (Thrombosis and Haemostasis, 1959)
The arrest of bleeding from small arteries or veins depends on the formation of a hemostatic plug made of platelets. In spite of recent information on the conditions required for platelet adhesion to various foreign surfaces, little is known about the precise mechanism of platelet adhesion to the lips of the vessel wound. The effectiveness of the hemostatic plug is due to the viscous metamorphosis of the agglutinated platelets.